CHROMATOGRAPHIC ANALYSIS OF CARBOXYLIC ACIDS IN THE FLOWERING SHOOTS OF SOME Vitex L. SPECIES - Mariia Shanaida; Alina Holenko (Acta Medica Leopoliensia)
Introduction. The genus Vitex L. counts more than 200 species of shrubs and trees common to subtropical areas of the Earth. Only fruits of Vitex agnus-castus L. are used in official medicine.